Work stress - Apolinario Zatizabal, Omar; Bravo Bravo, Ángel Orlando; Alvarado Márquez, Mariana de Jesús (Revista Universidad de Guayaquil, 2018)
Work-related stress is one of the major risks to health and safety are involved constant changes in regulations and the accelerated pace demanded by the different activities that relate to massive groups of people being the case of institutions of higher education you can create stress factors affecting the responsiveness and the working environment of employees. It is important to analyze its impact on the work environment and investing in stress prevention to ensure labor skills. Its main objective is to design a plan for prevention and stress management to improve the working environment of employees from the maintenance of the Faculty of Administrative Sciences.
Keywords: Work environment; job stress; maintenance area